THE STRENGTH OF THE GEOMAGNETIC-FIELD AT THE CRETACEOUS-TERTIARY BOUNDARY - PALEOINTENSITY RESULTS FROM THE DECCAN TRAPS (INDIA) AND THE DISKO LAVAS (GREENLAND) - SHAW, J; SHERWOOD, GJ; MUSSETT, AE; ROLPH, TC; SUBBARAO, KV; SHARMA, PV (TERRA SCIENTIFIC PUBL CO, 1991)
The lavas of the Deccan Traps (India) and Disko Island (West Greenland) were both erupted close to the Cretaceous-Tertiary (K-T) boundary. Ar-Ar dating has provided plateau dates of 67.1 +/- 1.1 Ma and 67.4 +/- 0.4 Ma for samples respectively near the base and near the top of the Deccan succession, and the uppermost flow of the Disco succession has a preliminary age of 64.7 +/- 1.4 Ma. Palaeointensities have been obtained from orientated samples from 47 Indian and 38 Greenlandic sites, using the SHAW (1974) technique with the ROLPH and SHAW (1985) correction for laboratory alteration. The intensity values show considerable scatter, but the mean virtual dipole moment calculated for the Deccan is 4.2 +/- 0.3 x 10(22) Am2 and for Disko is 5.8 +/- 0.6 x 10(22) Am2 compared to the present value of about 8 x 10(22) Am2. Studies of the variation of low-field susceptibility between -196-degrees-C and 700-degrees-C shows that the proportion of samples containing multi-domain magnetite is somewhat higher than in some younger lavas, suggesting hydrothermal alteration, which could account for some of the scatter in the palaeointensity values.